Individualizing basketball-specific interval training using anaerobic speed reserve: Effects on physiological and hormonal adaptations - Wang, C.; Ye, M. (International Journal of Sports Physiology and Performance, 2024)
Purpose: We compared the adaptive responses to supramaximal high-intensity interval training (HIIT) individualized according to anaerobic speed reserve (ASR), the 30-15 Intermittent Fitness Test (VIFT), and velocity associated with maximum oxygen uptake (MAS) to determine which approach facilitates more identical adaptations across athletes with different profiles.